Spatial vulnerability analysis for the first ply failure strength of composite laminates including effect of delamination. (15th January 2018) - Karsh, P.K.; Mukhopadhyay, T.; Dey, S.
Highlights: Effect of spatial variation in failure load (locational vulnerability) is analysed in composite laminates. Effect of delamination is addressed considering spatially varying failure loads. Effect of stochasticity is investigated on the failure strength of composite laminates. Abstract: The present investigation deals with the first ply failure strength of laminated composite plates for spatial variation of loading position, which can render a clear idea about the locational sensitivity of the loading positions in a two dimensional space. In this context, the effect of delamination is investigated on the failure strengths considering angle ply and cross ply laminates. A finite element model is developed based on different failure criteria of composites, such as maximum stain, maximum stress, Tsai-Hill, Tsai-Wu-Hahn and Tsai-Hill-Hoffman. An eight noded isoparametric quadratic element is considered in the present finite element formulation incorporating transverse shear and rotary inertia. Results are presented in deterministic as well as stochastic regime. For obtaining the probabilistic descriptions of failure strengths following different failure criteria, Monte Carlo simulation is carried out in conjunction with the finite element model following a non-intrusive approach. The variation of failure strength is portrayed considering the effect of stacking sequence, ply orientation, number of layers, degree of orthotropy and ply thickness. In this article, consideration of stochastic material and structural attributes along with critical service-life characteristics such as delamination for spatially varying loading positions provides a comprehensive understanding about the failure strength of composite laminates for practical applications.